Diet of the European eel Anguilla anguilla (Linnaeus, 1758) in two transitional waters of Southwestern Mediterranean - Derbal, Farid; Hamdi, Sandra; Rouag-Laouira, Lydia; Chaoui, Lamya; Kara, Mohamed Hichem (Zenodo, 2022)
Derbal, Farid, Hamdi, Sandra, Rouag-Laouira, Lydia, Chaoui, Lamya, Kara, Mohamed Hichem (2022): Diet of the European eel Anguilla anguilla (Linnaeus, 1758) in two transitional waters of Southwestern Mediterranean. Cybium 46 (1): 3-11, DOI:10.26028/cybium/2022-461-001, URL: http://dx.doi.org/10.26028/cybium/2022-461-001